Potensi Ekstrak Cincau Hijau (Premna oblongifolia Merr.) dalam Menstimulasi Pertumbuhan Bakteri Asam Laktat Saluran Pencernaan - Ginting, Friska Ekagia; Antara, Nyoman Semadi; Wijaya, I Made Mahaputra (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): September, 2020)
The green grass (Premna oblongifolia Merr), is a woody shrub plant mainly found in the forest. The main content of the plant is pectin, so green grass jelly is considered good source of dietary fiber, because the fiber can be fermented properly by digestive microflora (Gallaher, 2000). The fiber contained in green grass extract is believed to stimulate the growth of lactic acid bacteria in the digestive tract. The purpose of this study was to determine the potential of green grass jelly extract in stimulating the growth of digestive bacteria. The research was carried out in a laboratory with the treatment of adding concentrations of green grass jelly extract powder, and glucose as a control. The media used was Yeast-Pepton which added 1% glucose, green cincau extract powder 0.1%, 0.2%, 0.3%, 0.4%, 0.5%. Fermentation was carried out at 37 ° C with 18 hours fermentation time. The results showed that the concentration of the green grass extract 0.2% gave the best total lactic acid bacteria, this could because at this concentration the media had not increased the viscosity which inhibited bacterial growth. Keywords : green gras, pdigestive lactic acid bacteria, ectin.